The Contribution of Renewable Energy to International Security: A Preliminary Study (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
The world is experiencing a process of energy transition from fossil fuels to renewables. Such a transition is pushed by the necessity to face a global environmental challenge like climate change as well as pulled by constant research for reliable, affordable and sustainable energy security strategies. The energy transition will progressively introduce important changes in the geopolitical sphere, thus challenging some of the assumptions ruling the contemporary system of international relations. Among them, a critical issue is if the development of a renewable energy system would reduce or increase the risks of conflict. This preliminary study, which is based on a qualitative assessment of the available academic literature, examines the impact that a growing use of renewables might have in the framework of international security. The main conclusion is that renewables might give a positive contribution to international security by reducing the dependency system characterizing the current trade of hydrocarbon resources, mitigating the “resource curse” of energy exporting countries, and reducing greenhouse gas emissions, thus moderating the insurgence of all those risks associated with climate change.      Key words: Energy transition; renewables; energy security; resource curse; international security.